The Correlation Between Students’ Motivation and Their Speaking Achievement - Annisa, Rizka; Ilma, Ridha; Sartika, Eka (PROJECT (Professional Journal of English Education), 2025)
Speaking is a vital skill in language learning, and a student's motivation significantly influences their willingness and ability to improve their speaking Achievement. This study aimed to determine the significant correlation and influence of students' motivation on their speaking achievement. A quantitative research approach with a correlation design was employed. The population consisted of 246 eleventh-grade students at a private high school in Palembang. The researchers used a cluster random sampling technique to select the sample. Data were collected using the Attitude/Motivation Test Battery (AMTB) questionnaire and a speaking test. The results showed no statistically significant correlation between students' motivation and their speaking achievement, as the obtained correlation coefficient (r-obtained) of 0.106 was lower than the critical value (r-table) of 0.339. Additionally, the two-tailed significance level was .550, indicating that the p-value (.550) exceeded the threshold of .005. Therefore, the null hypothesis (H01) was accepted.